Geological Heritage and Geotourism in the Marbles region, Portugal: The emergence of new economic activities - Lopes, Luís (2015)
In recent years, Portugal, Alentejo and the marbles region in particular, have been promoted overseas as a tourist destination of excellence. Climate, historic and cultural heritage, cuisine, crafts, hosting, quality and quantity hotel facilities are arguments that support this promotion on the ground. Until the 21st century there was no significant record of unemployment in the marble region. Now, the based marble economy cannot create jobs enough to occupy the population and new proposals business has been developed. A strong artisanal production of organic food, recovering old traditions and making high quality products, handicraft in stone, wood, tin and pottery has been growing. There's also a reuse of quarries and surrounding land, In either case, the marble is always present. This work presents examples of actions implemented in the region contributed to minimize the negative impact left by the lower rate of human occupation in the ornamental stone sector. These examples can be replicated in analogous regions all over the World where the need to preserve old mining activity tools and techniques must strongly advised from now on. Initiatives such as the Route Shades of Marble begin to be known in Portugal and abroad. The Marble Museum of Vila Viçosa, located within the city perimeter, occupies a former quarry being ideal to in situ illustrate the techniques used to dismantle the marble for more than two thousand years. A five-star hotel applied local marble illustrating multiple combinations of textures, colors and patterns that they permit. Abandoned quarries are opportunities for wildlife that found conditions good enough to establish and develop. Nature observation tourism, in particular bird watching, it is also an alternative to consider, especially because the region his already in the route that comprises places where this activity has been established with a regular public. References Germano, D.; Lopes, L.; Gomes, C.; Santos, P. & Martins, R. 2014. O impacte das pedreiras inactivas na fauna, flora e vegetação da zona dos mármores: problema ou benefício? Callipole, 21, Vila Viçosa, in press. Lopes, L. & Martins, R. 2014. Global Heritage Stone: Estremoz Marbles, Portugal. From: Pereira, D., Marker, B. R., Kramar, S., Cooper, B. J. & Schouenborg, B. E. (eds) Global Heritage Stone: Towards International Recognition of Building and Ornamental Stones. Geological Society, London, Special Publications, 407, http://dx.doi.org/10.1144/SP407.10 Lopes, L.; Martins, R.; Falé, P.; Passos, J.; Bilou, F.; Branco, M. & Pereira, M. F. 2013. Development of a Tourist Route around the Mining Heritage of the Estremoz Anticline. From: Rosa, L.; Silva, Z. & Lopes, L., (eds), Proceedings of the Global Stone Congress, Key Engineering Materials Vol. 548 (2013) 348-362; Trans Tech Publications, Switzerland. http://dx.doi.org/10.4028/www.scientific.net/KEM.548.348